Moral Intelligence Inventory: A Moral Intelligence Measurement Tool for Public Junior High School Students - Asruro Rozak, Azza; Soejanto, Laily Tiarani; Khairul Bariyyah; Palasara Brahmani Laras (International Journal of Applied Guidance and Counseling, 2024)
Moral intelligence is the ability to differentiate between right and wrong, create exact choices, and behave ethically according to applicable norms and rules. This development is purposed to produce a moral intelligence inventory. This method applies Borg and Gall development model. The population of this research is students of junior high schools in Malang. Indeed, the sampling is decided through cluster random sampling, wherein 300 students were selected as the research sample. The data are analyzed using Product Moment Pearson analysis, Alpha Cronbach, normality test, and factor analysis. This development draws on a moral intelligence inventory product for junior high school students in Malang, which consists of 45 statement items. These met the criteria of moral intelligence inventory, validity test, and reliability test on a high scale with a 0.907 coefficient. Future research is suggested to improve moral intelligence inventory for elementary, senior high school, and vocational school students. They considered that these levels' development, age maturity, and learning process differ from junior high school. Additionally, the following researchers are expected to employ other theories that discuss moral intelligence to assist students in finding out their moral intelligence level. Keywords: Moral intelligence, vocational school, students.